THE EFFECT OF INTERNAL CONTROL SYSTEM ON AUDIT QUALITY IN PUBLIC ACCOUNTING OFFICES IN JAKARTA - Dedek Handoko; Juaniva Sidharta; Fenny B.N.L. Tobing (Fundamental Management Journal, 2023)
The purpose of this study was to determine whether there is an impact between the system of internal control and audit quality. The research method used was to quantify the population of all accounting firm employees in Jakarta, and since the population cannot be known, the sampling technique of Rao Purba was used. The sampling technique in this study used a no-probability sampling technique of randomly drawing a sample of 96 per 100 respondents. The analytical technique used was simple linear regression. The results show that the internal control system has a significant positive impact on audit quality. The conclusion is that the Jakarta audit company's internal control system can improve the audit quality well and harmoniously. Therefore, accounting firms want to be able to allocate tasks efficiently so as not to create additional workload for employees. Keywords: Internal Control System, Audit Quality, Public Accounting Firm